2020
DOI: 10.3389/fphar.2020.600132
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Profiling of Angiotensin II Type 1 Receptor With Mutations Associated to Atrial Fibrillation in Humans

Abstract: The AT1 receptor (AT1R) has a major role in the Renin-Angiotensin System, being involved in several physiological events including blood pressure control and electrolyte balance. The AT1R is a member of the G protein coupled receptors (GPCR) family, classically known to couple Gαq and engage β-arrestin recruitment. Both G protein and arrestin signaling pathways are involved in modulation of different downstream kinases. A previous study reported that mutations in the AT1R (A244S and I103T-A244S) were positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In fact, most Ang II physiological effects are mediated through AT1R [ 14 ]. AT1R is a GPCR that requires Ang II binding for its activation [ 14 , 15 , 25 ]. Therefore, it belongs to the canonical seven-transmembrane α-helical superfamily, with an intracellular C-terminal domain, an extracellular N-terminal domain, three intracellular loops (ICL1, ICL 2, ICL3), an amphipathic helix VIII, and three extracellular loops (ECL1, ECL2, ECL3) [ 13 , 14 , 26 ].…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, most Ang II physiological effects are mediated through AT1R [ 14 ]. AT1R is a GPCR that requires Ang II binding for its activation [ 14 , 15 , 25 ]. Therefore, it belongs to the canonical seven-transmembrane α-helical superfamily, with an intracellular C-terminal domain, an extracellular N-terminal domain, three intracellular loops (ICL1, ICL 2, ICL3), an amphipathic helix VIII, and three extracellular loops (ECL1, ECL2, ECL3) [ 13 , 14 , 26 ].…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
“…Polymorphisms in GPCRs were shown to be associated with different phenotypes and to predispose to certain types of diseases [ 15 ]. More than 700 mutations, that can overactivate or inactivate the receptors, have been identified and linked to more than 30 distinct human illnesses [ 15 ].…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…The release of Ang II is generally known to induce vasoconstriction, thirst and the release of aldosterone ( Culman et al, 1995 ) and has also been demonstrated to possess pro-inflammatory effects ( Ruiz-Ortega et al, 2001 ; Chen et al, 2006 ; Ruiz-Ortega et al, 2006 ; Wilkinson-Berka et al, 2019 ), which are all conveyed through the angiotensin II type 1 receptor (AT1R; Forrester et al, 2018 ). AT1 receptors are G-protein coupled receptors that ultimately trigger the release of Ca 2+ from the endoplasmic reticulum which results in the activation of protein kinase C (PKC) and additional kinase enzyme activation in the extracellular signal-regulated kinase (ERK1/2) pathway ( Simões et al, 2020 ). In contrast, the type 2 receptor (AT2R) is generally understood to act against AT1R, as it is known to elicit vasodilation through the generation of nitric oxide (NO) and contribute to cell survival ( Reinecke et al, 2003 ; Carey, 2017 ; Verma et al, 2019 ).…”
Section: Neuropeptides Most Relevant For Retinal Healthmentioning
confidence: 99%